The Impact of CYP2C9 and VKORC1 Polymorphism in Patient’s Response to Warfarin and Acenocoumarol - Jallul, M.S⋆, Mwada Mohamed; Dugani, PhD, Aisha Mohamed; Elgdhafi, MD, Elham Omran; Bashein, PhD, Abdulla Masood (Journal of Medical Biomedical and Applied Sciences, 2019)
Warfarin is commonly prescribed as oral anticoagulant medication for Libyan patients, the wide inter-individual variation between the patients in their response to oral anticoagulants is attributed to genetics factors, mainly polymorphisms in CYP2C9 and VKORC1. This study was aimed to assess the impact of genetic (CYP2C9*2, *3 and VKORC1- 1639G>A/ and 1173 C>T polymorphism), and non- genetic factors: age, and body mass index (BMI) in the response of Libyan patients using oral anticoagulants.A total of 100 patients with stable maintenance dose of warfarin or acenocoumarol were recruited during their routine follow up in anticoagulant clinic at Tripoli Medical Centre. CYP2C9 and VKORC1 variant alleles were screened by (HRM) real-time PCR, followed by DNA sequencing.The variant allele frequencies of CYP2C9*2, CYP2C9*3, and VKORC1 -1639G>A/1173C>T were 9.5%, 4.0%, 4.5%, and 37.0%, respectively.Carriers of VKORC1 (-1639 G>A, 1173 C>T) variant alleles required a significantly lower doses of oral anticoagulants compared with carriers of wild type, P value =0.04, and 0.019, respectively. No significant difference in dose requirement was found between carriers of wild type, and CYP2C9*2 and *3 variant alleles, P value =0.11 and 0.98, respectively.The multivariate regression model including age, BMI, VKORC1, and CYP2C9 genotype produced weak model for estimating the drug dosage (R2= 8.6%); and neither genetic nor non-genetic factors could be used as a predictor for estimation of oral anticoagulant dosage.Our data showed that VKORC1 variant alleles but not CYP2C9*2, *3 variant alleles significantly contributed to oral anticoagulant dose variability.